Density-dependent analytical equations of radiation shielding parameters for super alloys by linear regression analysis - M. Aygun; Z. Aygun (Ядерна фізика та енергетика)
Super alloys have great interest with good mechanical strength, surface stability, high operating temperatures, and high resistance to corrosion and oxidation features. In the study, new, reliable, and practical equations which give the radiation shielding parameters depending on the density of super alloys are obtained. For this analysis, MAR-247, MAR 302, Inconel 625, Inconel 718, Nimocast 75, WI-52, Inconel 617, Incoloy 800HT, Inconel 939, 713LC, and 7925A super alloys are chosen. The radiation shielding parameters such as linear attenuation coefficient, effective atomic number, half value layer, mean free path, and fast neutron removal cross-section are calculated by using Phy-X/PSD program. Then, new analytical equations providing the radiation shielding parameters by linear regression analysis are evaluated.